2021
DOI: 10.1111/ejn.15379
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of white matter lesions in cerebrovascular disease

Abstract: White matter lesions have been implicated in the setting of stroke, dementia, intracerebral haemorrhage, several other cerebrovascular conditions, migraine, various neuroimmunological diseases like multiple sclerosis, disorders of metabolism, mitochondrial diseases and others. While much is understood vis a vis neuroimmunological conditions, our knowledge of the pathophysiology of these lesions, and their role in, and implications to, management of cerebrovascular diseases or stroke, especially in the elderly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 204 publications
(294 reference statements)
0
21
0
Order By: Relevance
“…A higher neutrophil count one day after hospital admission was associated with sICH while a higher NLR was associated with parenchymal haemorrhage and sICH [ 33 ]. We postulate that the progression to poor outcomes despite good collateral status and successful reperfusion, e.g., in AIS patients with LAA, may be explained by other factors such as NLR [ 42 ] and severity of leukoaraiosis [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A higher neutrophil count one day after hospital admission was associated with sICH while a higher NLR was associated with parenchymal haemorrhage and sICH [ 33 ]. We postulate that the progression to poor outcomes despite good collateral status and successful reperfusion, e.g., in AIS patients with LAA, may be explained by other factors such as NLR [ 42 ] and severity of leukoaraiosis [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…40 Factors such as delayed onset-to-reperfusion time and leukoaraiosis have also been implicated. 3,41 Regardless, studies have shown that reperfusion therapy is safe for patients with diabetes and leads to better outcomes compared to patients who did not receive reperfusion therapy. 30,42 During the current coronavirus disease 2019 (CO-VID-19) pandemic, an increasing attention is being paid to the disproportionate burden on patients with pre-existing diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…1 The advent of reperfusion treatment, intravenous thrombolysis (IVT) and endovascular thrombectomy (EVT) offers the opportunity to significantly improve the outcomes after acute ischemic stroke (AIS). 2 Moreover, since 2015, in the era of EVT, an increasing attention has been paid to identifying patients or stratifying them based on the clinical profiles or imaging factors, 3,4 who are more likely to benefit from time-critical therapies. [5][6][7][8][9] As such, it is of clinical relevance to fully delineate the role of diabetes in AIS, in the setting of reperfusion therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The relevant literature reports multiple examples of clinical, biological, biochemical, and radiological factors with potential relevance to the prognosis for ischaemic stroke patients treated with mechanical thrombectomy [22,23]. The factors associated with a poorer prognosis following thrombectomy include: age, comorbitidies (HA, DM), previous stroke, stroke severity, the Alberta Stroke Program Early CT Score (ASPECTS), ischemic core volume, mismatch of ischemic core and hypoperfusion volume, white matter lesions, the location of the occlusion, collateral flow status and neutrophil lymphocyte ratio [5][6][7][8]24,25].…”
Section: Discussionmentioning
confidence: 99%